Ecosystem Understanding of the City-Human Being Relationship - Najder-Stefaniak, Krystyna (Studia Ecologiae et Bioethicae, 2022)
This paper presents the ecosystem understanding of the city-human being relationship. The author makes use of the paradigm of the ecosystem relationship in order to understand the city and human being as elements of the cultural and natural system. The concept of the ecosystem relationship, as defined by Edgar Morin, the French theoretician of complexity, plays an important role here. The paradigm of the ecosystem relationship makes us realize the complexity of dependencies in the dynamic, open and relatively isolated system of activity. Morin was inspired by Erwin Schrödinger’s discovery that the ecosystem co-organizes and takes part in the programming of the organisms within it. The social and natural system is the second crucial notion in this paper. It was coined as a result of interdisciplinary research conducted by Józef Marceli Dołęga, the founder of the Polish school of humanistic ecology and systemic sozology. The concept of transgression is yet another one important in my work. The term “transgressive man” was coined by Józef Kozielecki, a psychologist. Having understood transgression, we may see that man is capable of bestowing his presence on the present, future and past. The paradigm of the ecosystem relationship allows us to understand that a subject may direct its actions not only toward what is but also toward what may or should be. The conclusion is that we, as elements of the cultural and natural ecosystem, may enrich the city when we become part of it. Moreover, we may enrich ourselves when the city becomes part of our space.